2002
DOI: 10.1074/jbc.m200744200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Positively Regulates DNA Binding of the Carbon Catabolite Repressor Cre1 of Hypocrea jecorina(Trichoderma reesei)

Abstract: Cre1 of the ascomyceteCarbon catabolite repression is a means by which cells manage priority use of easy and fast metabolizable carbon sources over more complex ones. In Saccharomyces cerevisiae, mutations in MIG1 or in respective binding sites in Mig1 regulated promoters partially relieve the yeast from carbon catabolite repression (1-4). To form an active repressor complex, Mig1 requires the co-repressors Ssn6 (Cyc8)-Tup1 (5-8). Mig1 function is regulated by glucose-dependent nuclear import/export, Mig1 bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
90
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 49 publications
(47 reference statements)
2
90
1
1
Order By: Relevance
“…The basal transcription of xyn1 is subject to carbon catabolite repression mediated by carbon sources such as glucose and glycerol. As described previously (9,23), transcriptional activation can overcome carbon catabolite repression as xylose triggers induction even in the presence of glucose. A Cre1-dependent repression/derepression system is not involved in this activation, as the basal transcriptional level of xyn1 constitutively appearing in a Cre1-negative background (H. jecorina RUT-C30) still remains inducible by xylose (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basal transcription of xyn1 is subject to carbon catabolite repression mediated by carbon sources such as glucose and glycerol. As described previously (9,23), transcriptional activation can overcome carbon catabolite repression as xylose triggers induction even in the presence of glucose. A Cre1-dependent repression/derepression system is not involved in this activation, as the basal transcriptional level of xyn1 constitutively appearing in a Cre1-negative background (H. jecorina RUT-C30) still remains inducible by xylose (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…H. jecorina (T. reesei) QM9414 (ATCC 26921); RUT C-30 (ATCC 56756), due to a cre1 truncation, a glucose-derepressed strain (18) which could recently be complemented with cre1 to regain carbon catabolite repression (9); and N26, a ⌬ace1 mutant (VTT, Espoo, Finland) were used throughout this study. Strain TU-6 (12), a pyr4-negative mutant of QM9414, was used as a recipient for pyr4-mediated cotransformation experiments.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that transcription of the creA gene itself is negatively autoregulated in response to repressing carbon sources, leading to a reduced steady-state creA transcript level (17). However, the CCR-repressor function appears to be mainly controlled at the post-transcriptional or post-translational level (17)(18)(19)(20). In A. nidulans, strains mutant in two additional genes, creB and creC, exhibit some derepressed characteristics similar to those observed in loss-offunction creA mutants but also show a number of phenotypes not related to CCR (21,22).…”
mentioning
confidence: 99%
“…However, the genetic regulation of CreA/CRE1/CRE-1 appears to be fairly divergent amongst the filamentous fungi. In A. nidulans, the AMP-activated kinase, SnfA, is necessary for nuclear export of CreA (Brown et al, 2013), but in T. reesei, while phosphorylation of CRE1 is necessary for de-repression of target genes, this phosphorylation is not dependent on the SnfA homolog (Cziferszky et al, 2002(Cziferszky et al, , 2003.…”
mentioning
confidence: 99%